Incidental Large Pelvic Schwannoma Found on Rectal Cancer Staging - Jessica A. Chin; Maria A. Rojas; Jan P. Kaminski; Joaquin J. Estrada (World Journal of Colorectal Surgery)
We present the case of a 53-year-old man with newly diagnosed stage III rectal cancer who was found to have an incidental large pelvic schwannoma on staging imaging. Open enucleation and resection of the 11-cm schwannoma was performed to facilitate our oncologic resection, allowing for a single-stage procedure. Number of similar cases published: three.